PROGNOSTIC GENE SIGNATURE FOR INTERMEDIATE RISK PROSTATE CANCER - Li, Brian (My University, 2016)
The Gleason Score (GS) is a powerful predictor of outcome among prostate cancer patients. Patients with tumours graded with a GS of 2 to 6 have a much greater chance of survival compared to those with a GS of 8 to 10. A significant proportion (~40%) of men present with early stage GS 7 tumours (indicating intermediate risk) for whom prognosis is highly variable. Three gene signatures were derived from publicly available gene expression profiles of prostate cancers from the Swedish Watchful Waiting cohort: 1) The Genomic Grade Index consisted of the top 24 genes discriminating between high (8, 9 & 10) and low (≤ 6) GS tumours, 2) The Lethal Gene Score consisted of the top 24 genes discriminating between lethal and indolent disease within GS 7 tumours only, and 3) The network-based gene signature consisted of 88 genes. When these gene signatures were tested in silico on the gene expression profiles of GS 7 patients in both the SWW and the Mayo cohort, patients were stratified into high and low risk for recurrence. These results demonstrate that gene signatures are capable of differentiating low risk and high risk patients within GS 7 tumours. The prognostic capacity of our gene signature will be tested prospectively in a retrospective collection of archived prostate cancer tissue blocks from a phase 3 clinical trial, and it is hypothesized that the patients can be stratified into good and poor outcome groups. NanoString Technology will be used to quantify mRNA values for the signature genes on selected paraffin blocks. Expression values of candidate genes will be correlated with patients’ long-term follow-up information to derive a clinically meaningful signature. Outcome will be defined as biochemical recurrence or metastatic event. The goal of this study is to identify multiple genes whose expression could be formulated into a clinically applicable assay, the implementation of which could serve to better stratify intermediate risk prostate cancer patients for appropriate treatment.
Keywords: Prognostic Gene Signature; Prostate Cancer